Decentralization and sub-municipal government in South- Eastern European countries - Klarić, Mirko, pravnik (2021)
True this paper it would be analyzed sub-municipal government as a organizational form of local governance with comparative perspective, and elements which generally formed sub-municipal government as a tools for delivery of local public services and managing of local initiatives which are important for the local community. These two roles are crucial for understanding of dynamic in sub-municipal government. Special focus would be held on sub-municipal government in South- Eastern European countries, which they have a common history and institutional framework, with the main question: how can sub-municipal government contribute to strengthening of decentralization and democratic processes in the local community directly and, indirectly in whole society. Self-government systems which are highly decentralized usually have developed sub-municipal government. On the other side, in centralized countries sub-municipal government usually has reduced role which is connected with managing of public tasks connected with local community needs. The main question is how sub-municipal government can improve decentralization, and how those efforts at the end of the day contribute to better development of whole society.
U radu se analizirala institucija podopćinskog poglavarstva kao organizacijski oblik lokalne uprave sa komparativnom perspektivom i elementi koji su općenito činili podopćinsku vlast kao oruđe za pružanje lokalnih javnih usluga i upravljanje lokalnim inicijativama važnim za lokalna zajednica. Ove dvije uloge su ključne za razumijevanje dinamike u podopćinskoj vlasti. Poseban fokus stavljen je na podopćinske vlasti u zemljama jugoistočne Europe, koje imaju zajedničku povijest i institucionalni okvir, s glavnim pitanjem: kako podopćinska vlast može pridonijeti jačanju decentralizacije i demokratskih procesa u lokalnoj zajednici izravno i neizravno u cijelom društvu. Sustavi samouprave koji su visoko decentralizirani obično imaju razvijenu podopćinsku upravu. S druge strane, u centraliziranim zemljama podopćinska vlast obično ima smanjenu ulogu koja je povezana s upravljanjem javnim zadacima povezanim s potrebama lokalne zajednice. Glavno pitanje je kako pod-općinska vlast može poboljšati decentralizaciju i kako ti napori na kraju dana doprinose boljem razvoju cijelog društva.
Bibliografske bilješke uz tekst ; bibliografija: 59 jed.
Summary ; Sažetak.
Keywords: Lokalna uprava -- Decentralizacija; Zemlje Jugoistočne Europe